Criteria for mixed grids in computational fluid dynamics - Doescher, Erwin; de Campos Velho, Haroldo F.; Ramos, Fernando M. (Elsevier B.V., 2006)
The finite volume method is used as a numerical method for solving the fluid flow equations. This method is appropriate to employ under structured and unstructured meshes. Mixed grids, combining both types of grids, are investigated. The coupling of different grids is done by overlapping strategy. The computational effort for the mixed grid is evaluated by the CPU-time, with different percentage of covering area of the unstructured mesh. The present scheme is tested for the driven cavity problem, where the incompressible fluid is integrated by calculating the velocity fields and computing the pressure field in each time step. Several schemes for unstructured grid are examined, and the compatibility condition is applied to check their consistency. A scheme to verify the compatibility condition for the unstructured grids is presented. (c) 2006 IMACS. Published by Elsevier B.V. All rights reserved.
Keywords: computational fluid dynamics; mixed grids; finite volume method; incompressible fluid; compatibility condition